Levels and sources of PCDDs, PCDFs and dl-PCBs in the water ecosystems of central Poland — A mini review - Marek Zieliński; Joanna Kamińska; Marta Czerska; Danuta Ligocka; Magdalena Urbaniak (International Journal of Occupational Medicine and Environmental Health, 2014)
Polychlorinated dibenzo-p-dioxins (PCDDs) and dibenzofurans (PCDFs) are unwanted by-products in a variety of industrial and thermal processes. They have been present on Earth long before the human era, since they may be also formed as a result of forest fires or volcanic explosions. Polychlorinated biphenyls (PCBs) in turn, have been intentionally produced by humans. Poland was a minor producer of PCB mixtures (Chlorofen and Tarnol), which were a source of direct and indirect environmental diffusion with PCB and less with PCDDs/PCDFs. Industrial accidents with PCDDs/PCDFs were absent in Poland. Their stability and resistance to thermal breakdown made them very dangerous for environment and, in consequence, due to their environmental persistence, bioaccumulation and biomagnification in the terrestrial and aquatic food chains, to humans. Humans may become affected by PCDDs/PCDFs and PCBs through environmental (soil and water contamination, fish and food), occupational (incinerators; pulp, paper and metallurgy industry; copper production), or accidental (Seveso accident) exposure. The aim of this review was to evaluate environmental hazard caused by PCDDs, PCDFs and dioxin-like-PCBs in the central region of Poland based on the accessible data on diffusion of those compounds in sediments and riverine, reservoir and storm water from our previous studies and discussed in the context of other achievements in Poland and elsewhere.